Efektivitas Media Gambar Anggota Tubuh Perbantuan Aughmented Reality Dalam Meningkatkan Kemampuan Kosa Kata Bahasa Inggris Anak Kelompok B Di TK IT Annida - Elma Octaviani; Ratu Yustika Rini; Moh. Fikri Tanzil Mutaqin (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
This study was conducted based on the importance of English language skills for young children as part of 21st-century competencies. However, English learning in early childhood settings particularly vocabulary related to body parts—still faces challenges due to the use of conventional methods that are less engaging and do not utilize technological support. To address this issue, this research examined the effectiveness of body-part picture media assisted by Augmented Reality (AR) in improving English vocabulary skills among Group B children at TK IT Annida.A quantitative approach was employed using a quasi-experimental design with a one group pretest posttest model. The sample consisted of 10 children from Group B. The instrument used was a vocabulary test administered before and after the intervention. The learning activities integrated picture media of body parts with AR technology, providing interactive and visually appealing 3D representations.The findings indicate a significant improvement in the children’s English vocabulary after using AR-based picture media. The percentage of children in the “good” category increased from 20% to 66.67%, while the “poor” category decreased from 53.33% to 6.67%. The t-test results showed a significance value of 0.000 (<0.05), confirming a significant effect of AR-assisted picture media on vocabulary improvement. Therefore, AR media is proven effective and suitable as an innovative tool for English language learning in early childhood education